2021
DOI: 10.1002/nafm.10582
|View full text |Cite
|
Sign up to set email alerts
|

Enumerating Predation on Chinook Salmon, Delta Smelt, and Other San Francisco Estuary Fishes Using Genetics

Abstract: The establishment of non-native predator fish is a worldwide phenomenon often having adverse effects on native species. Trophic interactions are complex, and uncertainty is a common theme in discussions of non-native predator management. Several fishes of the San Francisco Estuary have experienced significant declines in recent decades due to multiple factors, including habitat alteration and predation. The role of predation as a direct cause of mortality remains an open question, as does whether habitat condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Non-native fish have high relative abundance in the lower San Joaquin River and south Delta (Brown and Michniuk 2007), resulting in a prey base dominated by nonnative fish. In the north Delta, which remains a stronghold for native fish species (Moyle et al 2012), Brandl et al (2021) found that FO of native fish prey was 51% higher than what Michel et al (2018) observed. On the Stanislaus River, native species have higher relative abundance than in the lower San Joaquin River, especially during the juvenile Chinook Salmon migration season when estimates of abundance can range from 127,000 to over 2 million (Pilger et al 2019).…”
Section: Predator Dietsmentioning
confidence: 91%
See 4 more Smart Citations
“…Non-native fish have high relative abundance in the lower San Joaquin River and south Delta (Brown and Michniuk 2007), resulting in a prey base dominated by nonnative fish. In the north Delta, which remains a stronghold for native fish species (Moyle et al 2012), Brandl et al (2021) found that FO of native fish prey was 51% higher than what Michel et al (2018) observed. On the Stanislaus River, native species have higher relative abundance than in the lower San Joaquin River, especially during the juvenile Chinook Salmon migration season when estimates of abundance can range from 127,000 to over 2 million (Pilger et al 2019).…”
Section: Predator Dietsmentioning
confidence: 91%
“…Nonetheless, we were able to document important predator-prey interactions on the Stanislaus River over 3 years. Although we successfully identified most of the recovered diet items, some rarer, small-bodied (and highly digestible) fishes could have been missed (Brandl et al 2021). In this study we visually identified and genetically validated discrete diet items, which likely yielded precise estimates of consumption for larger prey fishes (i.e., juvenile Chinook Salmon and lamprey), but estimates for smaller (larval) fishes that were more digestible should be considered conservative.…”
Section: Study Limitationsmentioning
confidence: 98%
See 3 more Smart Citations